TEKNIK SELF-INSTRUCTION UNTUK MENINGKATKAN KEPERCAYAAN DIRI PESERTA DIDIK SMP - Sari, Yunita Puspita; Mahmudah, Ulya; Djannah, Wardatul (Universitas Sebelas Maret, 2017)
This research aims to investigate the effectivity of self-instruction technique to improve self-confidence of junior high school students. Self-confidence in this research was confidence in learning. The research was a single-case experimental research A-B design. The subject of this research were two subjects which is chosen using purposive sampling technique. The data was collected using self-confident questionare, observation, and interview. Then the data was analyzed using statistic analysis with percentages techniques and clinical analysis. The analysis showed that the calculations using percentages analysis techniques in subject 1 shows the percentages change in the behavior of self-confidence in learning at 62,5%, subject 2 shows change of self-confodencein learning at 61,5%. The result of percentage analysis are supported by the result of clinical analysis, teachers and friends of the subject as significant others in the school states that in each of the research subjects experienced a increase in level of confidence in learning. This shows that there is a difference between the baseline data measurement phase with the data post intervention measurement of self-confidence. Then the hypothesis is proven. The conclusions of this research that self-instruction technique are effective to improve self-confidence of junior high school students.